RUSSIAN STRATEGY IN CENTRAL ASIA - INIUTIN, Ivan (CENTRAL ASIA AND THE CAUCASUS, 2006)
The mass unrest in Kyrgyzstan which escalated into an anti-government coup, the events in the Uzbek city of Andijan, and the presidential election in Kazakhstan, which also took place in 2005, drew the attention of the world community to the Central Asian countries. Whereby the situation in this section of the “arc of instability,” which encompasses the south of the Russian Federation, is arousing very justifiable concern among Russians. After all, the matter does not concern some abstract corner of the earth, but a significant part of the former Soviet Union, four million square kilometers in area and with a population of more than 50 million people (seven million of whom are Russian-speaking citizens). Historical development and long years of coexistence with the peoples of Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan have made Russia an interested party in their fates. This is shown by the special demands of official Moscow’s foreign policy in Central Asia and gives rise to the need for its rapid and targeted adjustment. Conceptually, Russia’s strategy in the region is aimed at achieving the strategic goals envisaged in the foreign policy conception approved by the country’s president. The following tasks are of paramount importance: —ensuring that alternative security systems are not created in Central Asia without the Russian Federation’s participation, and counteracting attempts by third countries to reinforce their military presence in this region. —expanding Russian capital in the key branches of the economy of the region’s republics and ensuring the unhindered functioning of their transportation corridors and distribution lines, including those relating to fuel and energy. —providing universal protection of the rights and interests of Russian citizens and compatriots, and strengthening the status of the Russian language and culture of Russia’s nationalities. —consolidating multilateral structures with the participation of the Russian Federation and strengthening their key significance in ensuring stability and security on the state’s southern borders. When carrying out the designated tasks, not only must the objective difficulties created by globalization be dealt with, but also problems generated by local development. Globalization has reopened this region, since for several centuries it was closed off to the rest of the world by Afghanistan, Iran, China, and Russia. New actors have appeared with significant financial and military-political potential. As for the local specifics, their most distinguishing feature is monopolization of power by a narrow circle of people, the family-clan composition of the ruling elite, and the impetuous striving for a leader personality cult.